INITIAL GROWTH AND COMPETITIVITY OF CORN WITH CONCURRENT PLANT AFFECTED BY THE GENOTYPE AND MASS OF SEEDS (Revista de Ciências Agroveterinárias, 2004)
The aim of this work was to verify the effect of seeds mass in different genotypes of corn over the emergency and initial growing speed of plants, as well as over the ability of the culture in competing with concurrent plant. For that, two experiments were carried out in the green house at Experimental Station in Canoinhas-SC/Epagri, Brazil. Seeds of open pollination varieties ‘Cepaf 06’ and ‘Sol da Manhã’ and the hybrids ‘Speed’ and ‘AGN- 35A42’ were used. The seeds were classified in two mass categories, seeds with mass 220-270mg and seeds with mass 370-420mg. In both experiments the emergency and initial growing speed of corn plants were evaluated. In the second experiment the ability of corn plants in suppressing the growing of the concurrent plant (soybean) was also evaluated. It was verified that the high mass of corn seeds provides the greater initial growing speed of plants and that the seeds mass of corn affect the competition of the culture with the concurrent plant at the beginning of the development cycle in genotype that show low initial growing speed.
Keywords: Zea mays L.; cultural management of weeds; competitive ability; competition.